2019
DOI: 10.1002/adma.201902393
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Arrays of Transition Metal Nitride Nanocrystals

Abstract: The synthesis of low‐dimensional transition metal nitride (TMN) nanomaterials is developing rapidly, as their fundamental properties, such as high electrical conductivity, lead to many important applications. However, TMN nanostructures synthesized by traditional strategies do not allow for maximum conductivity and accessibility of active sites simultaneously, which is a crucial factor for many applications in plasmonics, energy storage, sensing, and so on. Unique interconnected two‐dimensional (2D) arrays of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 33 publications
0
74
0
Order By: Relevance
“…2D arrays of NbN nanocrystals were synthesized using a salt‐templating method, as reported previously. [ 50 ] Briefly, the KCl salt powder coated with an Nb salt precursor was annealed in the ammonia atmosphere to obtain NbN@KCl. After removing the salt with deionized water, the 2D arrays of NbN nanocrystals are readily dispersed in water (inset of Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…2D arrays of NbN nanocrystals were synthesized using a salt‐templating method, as reported previously. [ 50 ] Briefly, the KCl salt powder coated with an Nb salt precursor was annealed in the ammonia atmosphere to obtain NbN@KCl. After removing the salt with deionized water, the 2D arrays of NbN nanocrystals are readily dispersed in water (inset of Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…[ 173 ] Xiao et al reported STM‐synthesized 2D arrays metal nitrides (CrN, TiN, and NbN) that demonstrated promising application in the Li‐S battery ( Figure ). [ 174 ] The unique interconnected structure of these materials with high conductivity allowed both fast ion and electron transport. The NbN‐based device achieves a high specific capacity of 1000 mAh g −1 as well as good stability even with a high areal sulfur loading over 5 mg cm −2 .…”
Section: Applicationsmentioning
confidence: 99%
“…Considering the high electron conductivity of NbN‐based host, we assume the removal of current collector may be possible in the future, which could further improve the volumetric energy density of the cell. We have previously reported the use of similar NbN porous arrays in Li−S battery cathodes [32] . Combined with the results reported above, there is a possibility to design a Li−S battery with both electrodes utilizing NbN or other TMN arrays as frameworks for both, Li and S deposition.…”
Section: Figurementioning
confidence: 73%
“…In this work, we report on a stable Li‐metal anode composed of 2D arrays of NbN nanocrystals as a Li host. Combining advantages of both, zero‐dimensional (0D) and 2D morphologies, interconnected 2D arrays of few‐nanometer NbN nanocrystals were synthesized using a topochemical method in ammonia on a salt template, [32] providing both high metallic conductivity and abundant ion transport channels. With 10 % Ti 3 C 2 MXene as a conductive binder, which also helps improve the mechanical strength of the film, [33] a flexible freestanding NbN‐based host was fabricated followed by electrochemical Li deposition to precisely load and tune the Li amount, forming a Li‐metal anode.…”
Section: Figurementioning
confidence: 99%